Oral N-acetylcysteine decreases IFN-γ production and ameliorates ischemia-reperfusion injury in steatotic livers - Liggett, Jedson R.; Kang, Jiman; Ranjit, Suman; Rodriguez, Olga; Loh, Katrina; Patil, Digvijay; Cui, Yuki; Duttargi, Anju; Nguyen, Sang; He, Britney; Lee, Yichien; Oza, Kesha; et al. (Frontiers in Immunology, 2022)
Type 1 Natural Killer T-cells (NKT1 cells) play a critical role in mediating hepatic ischemia-reperfusion injury (IRI). Although hepatic steatosis is a major risk factor for preservation type injury, how NKT cells impact this is understudied. Given NKT1 cell activation by phospholipid ligands recognized presented by CD1d, we hypothesized that NKT1 cells are key modulators of hepatic IRI because of the increased frequency of activating ligands in the setting of hepatic steatosis. We first demonstrate that IRI is exacerbated by a high-fat diet (HFD) in experimental murine models of warm partial ischemia. This is evident in the evaluation of ALT levels and Phasor-Fluorescence Lifetime (Phasor-FLIM) Imaging for glycolytic stress. Polychromatic flow cytometry identified pronounced increases in CD45+CD3+NK1.1+ NKT1 cells in HFD fed mice when compared to mice fed a normal diet (ND). This observation is further extended to IRI, measuring ex vivo cytokine expression in the HFD and ND. Much higher Interferon-γ expression is noted in the HFD mice after IRI. We further tested our hypothesis by performing a lipidomic analysis of hepatic tissue and compared this to Phasor-FLIM imaging using “long lifetime species”, a byproduct of lipid oxidation. There are higher levels of triacylglycerols and phospholipids in HFD mice. Since N-acetylcysteine (NAC) is able to limit hepatic steatosis, we tested how oral NAC supplementation in HFD mice impacted IRI. Interestingly, oral NAC supplementation in HFD mice results in less hepatic steatosis as evident on T1 weighted magnetic resonance imaging (MRI), improved hepatic enhancement using contrast-enhanced MRI compared to HFD fed mice, and normalization of glycolysis demonstrated by Phasor-FLIM imaging following. This correlated with improved biochemical serum levels and a decrease in IFN-γ expression at a tissue level and from CD45+CD3+CD1d+ cells. Lipidomic evaluation of tissue following IRI in the HFD+NAC mice demonstrated a drastic decrease in triacylglycerol, suggesting downregulation of the PPAR-γ pathway.